The impact of migration on the cultural heritage and identity.The example of the Croat (sub)ethnic group Bunjevci - Černelić, Milana (Array, 2012)
The paper deals with the (sub)ethnic group of Bunjevci, inhabiting today different territories of southeastern Europe, as the result of the mobility on the Balkans throughout 17th century. The etnonym Bunjevci stands for a group of ethnic Croats, originating from Dalmatia, southeastern Bosnia and Herzegovina, forming three branches of the ethnic group of Bunjevci known as the Dalmatia, Primorje/Lika and Danube area Bunjevci. The holistic approach to the research of their cultural heritage, and the ethnocultural processes through which the Bunjevci have been formed as a distinct ethnic group, could contribute to the better understanding of the way in which the identity of an ethnic group has been, and is being, formed, as well as in which the manifold identites of each particular branch have been constructed as the consequence of the migration processes. The paper points to the differences in construction of the Bunjevci branches' identities, based on the analysis of certain elements of their cultural heritage, which stand as a symbol of the collective identity as well as the subjective aspects of their identity. The focus is on the differences in the attitude of each branch to certain elements of their common cultural heritage taking into consideration the differences which are the result of their migration mobility. Consequently, the influence of the ethnic, cultural, social, historical, political, and ecological factors on the construction of the identity of each Bunjevci branch is discussed, outlining the differences in the process of creation of their identity, from objective as well as subjective point of view, based on the examples of some specific elements of the cultural heritage of Bunjevci.